A Study on the Place Attachment of Golf Club Members - Chen, Chun; Lin, Shu-Wang; Hsu, Shih-Yun; Wu, Chi-Hsuan (Frontiers in Psychology, 2020)
The purpose of this study is to explore the members of the golf clubs in the central region of Taiwan and find out if their activities are involved in the depth, whether they affect the degree of place attachment and add two factors of activity experience and experience value to explore more theoretical framework. A questionnaire survey was used to collect 534 samples from golf clubs in central Taiwan for analysis and use of research tools: Activity Involvement scale, Place Attachment scale, Likert psychological scale. The results of the study show that (1) activities involvement has a significant positive impact on place attachment, activity experience, and experience value; (2) activity experience has a significant positive impact on experience value; (3) experience value has a significant positive impact on place attachment. This result verifies the theory that activity involvement impacts place attachment. It is suggested that the relevant units should strengthen the incentives involved in the activities and strengthen the value of the leisure experience so as to facilitate the development of related industries in the future.